Are you overpaying your academic executive team? A method for detecting unmerited academic executive compensation. Issue 3 (2nd July 2016) - Pearce, Joshua
Abstract : University tuition fees and student debt have risen in part due to rapid expansion of university administration compensation. This study provides a novel methodology for detecting inappropriate executive compensation within universities. The usefulness of academic ideas is openly ranked using the h-index. By comparing the ratio of academic executive pay to their h-index a dollar per value of academic impact can be found. If the university compensation system is appropriately calibrated, the impact/ increases with faculty rank and continues to improve into the executive team. Analysis is provided for vice presidents of research of the ten largest state universities in America. The results suggest that 50% of these public universities are overcompensating their executives. A case study is presented of the most egregious discrepancy around compensation of >3.1 million/year. The methodology was shown to be a quick and inexpensive way to ascertain if further investigation is necessary at an individual university.